I once wished that I was an only child Looking positively on sibling rivalry. - Clutario, Warren A., et al.; Pariña, Chulia Mari O. (Tacloban City Warren A. Clutario, 2010)
This study, in summary, is about Sibling Rivalry, understanding its occurrence, finding out the reasons behind its occurrence and discovering its effects. The researchers have gathered studies speaking about the nature of sibling rivalry. There are also existing studies that make mention of the causes and effects of Sibling Rivalry. The researchers conducted interviews with the aid of an interview schedule. The respondents of the study were individuals aged 18 and above residing in Tacloban City and Leyte, Leyte. Through a series of interviews, the researchers were able to gather data from the respondents about their understanding of Sibling Rivalry, their reasons as to why they consider a particular sibling as their rival, also relaying their feelings toward their sibling and parents about this situation, and how they try to handle the situation. They also made mention of the effects it had towards them, may it be negative or positive.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban
Keywords: Social Science